Effect of support on the catalytic activity of WOx promoted Pt in green diesel production - Janampelli, Sagar; Darbha, Srinivas (Molecular Catalysis, 2018)
Platinum and WOx-promoted platinum supported on SiO2-Al2O3, Al2O3, AlPO4-5 and ZrO2 catalysts were prepared by wet impregnation method and investigated for deoxygenation of oleic acid (OA, a representative fatty acid) producing diesel-range hydrocarbons. Support and WOx influenced the textural, electronic and catalytic properties of Pt. WOx promoted the deoxygenation activity through hydrodeoxygenation pathway. Structure-activity correlations revealed that metallicity of Pt and acidity of the catalyst are crucial in determining the catalytic performance and product selectivity. Among the catalysts tested, 4Pt-8WO(x)/ZrO2, having adequate metal dispersion and electron rich Pt (desired for hydrogen splitting), reduced WOx species (W5+;-desired for OA activation) and less amount of strong acid sites (desired to avoid hydrocracking) showed highest catalytic deoxygenation performance (OA conversion = 100 mol% and C18 hydrocarbon selectivity = 89.4% at 260 degrees C and 20 bar H-2 pressure). The study reveals that support plays a crucial role in determining the catalytic performance of platinum. (C) 2017 Elsevier B.V. All rights reserved.